2021
DOI: 10.1016/j.ajem.2020.11.058
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil to lymphocyte ratio, lymphocyte to monocyte ratio and platelet to lymphocyte ratio to predict the severity of COVID-19

Abstract: Introduction In this study, we aimed to investigate and compare the prognostic impacts of C-reactive protein (CRP), white blood cell (WBC) count, neutrophil (NEU)-to-lymphocyte (LYM) ratio (NLR), platelet-to-lymphocyte ratio (PLR), Red Cell Distribution Width (RDW) biomarkers in laboratory-confirmed COVID-19 cases as well as to explore the most useful diagnostic biomarkers and optimal cutoff values in COVID-19 patients. Methods A total of 233 patients were admitted to E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
134
3
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(182 citation statements)
references
References 15 publications
16
134
3
5
Order By: Relevance
“…Severe subjects had a higher NLR compared to Non-Severe patients, similar to the results obtained by others [25][26][27], and above the mean (3.27, 95% CI: 1.99-4.55) reported in a meta-analysis [28].The sensitivity (66%) and speci city (48%) were however fair for this indicator and below the levels reported for these parameters elsewhere [29,30]. Despite this, neutrophilia is the hallmark of severe COVID-19.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Severe subjects had a higher NLR compared to Non-Severe patients, similar to the results obtained by others [25][26][27], and above the mean (3.27, 95% CI: 1.99-4.55) reported in a meta-analysis [28].The sensitivity (66%) and speci city (48%) were however fair for this indicator and below the levels reported for these parameters elsewhere [29,30]. Despite this, neutrophilia is the hallmark of severe COVID-19.…”
Section: Discussionsupporting
confidence: 88%
“…The PLR parameter reveals changes in platelet and lymphocyte counts because of acute in ammatory and pro-thrombotic conditions [36]. PLR levels associated with severe COVID-19 were within the range, since they were either higher [1,25,37] or lower [29] than the reference. PLR was higher in men, with a sensitivity of 71% (only 37% in women) and a speci city of 41%, (76% in women), which was suggestive of a different cytokine storm in COVID-19 patients [38] pending on the sex.…”
Section: Discussionmentioning
confidence: 99%
“…Although the definitive diagnosis of COVID-19 disease is the RT-PCR test, many routine and non-routine biological and biochemical parameters have been examined for their diagnostic values and clinical outcomes [ [2] , [3] , [4] , [5] , [6] , [7] ]. In the Cochrane database, 21 studies that include the laboratory data of 56,585 non-COVID-19 patients and 14,126 COVID-19 patients were reviewed.…”
Section: Discussionmentioning
confidence: 99%
“…Many diagnostic and prognostic biomarkers associated with COVID-19 disease have been revealed and investigated in the literature. These include D-dimer, C-Reactive protein (CRP), neutrophil count, leukocyte count, lymphocyte ratio, neutrophil-to-lymphocyte ratio, ferritin, procalcitonin and others not routinely tested in the diagnosis and clinical prognosis of COVID-19 [ [2] , [3] , [4] , [5] , [6] , [7] ].…”
Section: Introductionmentioning
confidence: 99%
“…AST [99][100][101], creatinine [102][103][104], fibrinogen [105][106][107], neutrophils [108,109], and respiratory rate [14,110] were reported to be positively related to the severity of COVID-19. Murat et al found that lymphocyte and platelet levels were higher in positive COVID-19 patients, while C-reactive protein (CRP) was higher in COVID-19negative patients [111]. Wang also found that lower lymphocyte counts and elevated CRP were risk factors for severity [112].…”
Section: Discussionmentioning
confidence: 99%